Literasi Media sebagai Solusi Tabayyun Berita Hoax di Media Sosial pada Mahasiswa FDK - Husnia Amro Br Sinaga; Anang Anas Azhar (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This research explores the media literacy skills of students of the KPI FDK UIN North Sumatra in responding to the spread of hoax news on social media. Using a qualitative descriptive approach, data was collected through interviews and observations. The research results show that students have a strong understanding of media literacy, which is reflected in their ability to analyze message structure, source credibility, and the purpose of digital content. They also tend to be critical and skeptical of the news circulating, by first cross-checking it through various official sources, such as government websites and verified news portals, before sharing it with others. Although media literacy education makes a positive contribution in raising awareness, challenges such as user anonymity and the proliferation of citizen journalism demand deeper evaluative skills. This research emphasizes the importance of applying the tabayyun (verification) principle as a basis for assessing information responsibly. Furthermore, this research shows that students act as agents of change by creating educational content on social media, holding digital literacy campaigns, facilitating discussions in the community, and becoming companions for peers and local communities in recognizing and rejecting false information. These various efforts show the active contribution of students in fighting disinformation and increasing public literacy regarding hoaxes.